Predicting Participation in Volunteering Based on Personality Characteristics - Hanif Akhtar (Journal of Educational, Health and Community Psychology, 2019)
The main purpose of this study was to find out whether big five personality traits can predict the participation in volunteering. A total of 420 participants consisting of 215 volunteers and 205 non-volunteers from various regions in Indonesia completed measures of the Big Five personality traits. The preliminary analysis using independent sample t-test found that the extraversion, agreeableness, conscientiousness, emotional stability, and openness of volunteer samples were significantly higher than non-volunteer samples. Binary logistic regression analysis then was used to examine whether each of big five personality traits was able to predict the participation to be volunteer. The logistic regression model was statistically significant, Ï‡2 = 67,102, p < ,01. The model explained 19,7% (Nagelkerke R2) of the variance in volunteer participation and correctly classified 64% of cases. Increasing extraversion and conscientiousness was significantly associated with an increased likelihood of volunteer participation. Thus, certain personality characteristics can predict participation in volunteering